Compaction of powders of titanium nitride nanopowder synthesis plasmodynamic by spark plasma sintering - Sivkov A. A. Aleksandr Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich; Usikov A. I. (2012, 2012)
Title screen.